Dinamika Konflik dan Jejak Perdagangan Senjata Di Tanah Papua - Latif, Syahrul Akmal; Shiddiqy, Muhammad Arsy Ash (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
This research describes the conflict dynamics and traces of the arms trade in Papua. Conflict and violence in Papua have become a kind of tangled thread and is a vertical conflict that has been going on for more than 50 years. The primary reason behind this conflict stems from the aspiration for an "Independent Papua,” which was fought for by the Free Papua Organization (OPM) but is now termed by the government as an armed criminal group (KKB). This conflict is also heating up with the existence of Freeport and issues of racial discrimination against Papuan students in various regions in Indonesia. The armed conflict in Papua continues to increase, and victims come from civil society and various professions, ages, genders, religions, and ethnicities, primarily indigenous Papuans. This conflict has threatened peace efforts in Papua, Indonesia, and internationally. The intensification of the conflict is strongly linked to the rise in illegal trade of firearms and ammunition (PSAA) within the region of Papua. The primary purpose of this article is to provide an explanation and analysis of the conflict dynamics in Papua, with a particular focus on investigating the presence and impact of the arms trade within the region. The research employed a descriptive qualitative approach to empirically depict all aspects of the research problem. The study's findings and conclusions reveal the prevalence and implications of the illegal trade in firearms and ammunition that occurs in Papua involves members of the TNI and POLRI, legislators, ASN, and civil society from various professions. Weak internal monitoring and evaluation of the TNI and POLRI institutions have contributed to the increase in PSAA in the land of Papua.